Wavelength-dependent chlorine photolysis and subsequent radical production using UV-LEDs as light sources. (1st October 2018) - Yin, Ran; Ling, Li; Shang, Chii
Abstract: UV-LEDs are considered as the most promising UV light sources, because it has the potential to replace conventional UV lamps in some water treatment applications in the foreseeable future. In this study, UV-LEDs at four wavelengths in the UV-C or near UV-C range (i.e., 257.7, 268, 282.3, and 301.2 nm) were used to investigate the wavelength-dependency on chlorine photolysis and its subsequent radical formation. The fluence-based photodecay rates of hypochlorous acid (HOCl) and hypochlorite (OCl − ) were monotonically correlated to their molar absorption coefficients and quantum yields, and the chlorine photodecay rates were much more significantly affected by molar absorption coefficients ( β = 0.949) than quantum yields ( β = 0.055). An empirical model that incorporated the chlorine photodecay rate constants, quantum yields, and molar absorption coefficients of HOCl and OCl − was established, validated and then used to predict the chlorine photodecay rate at any wavelength (257.7–301.2 nm) and pH (5−10). The modelling results suggested that the maximum fluence-based rate constant (1.46 × 10 −4 m 2 J −1 ) was obtained at 289.7 nm and pH 9.95. The wavelength dependency was larger at alkaline pH than at acidic pH, and the pH dependency was the largest at the longest wavelength. The formation of hydroxyl radicals (HO·) and reactive chlorine species (RCS) decreased with increasing wavelength at pH 6, and increased with increasing wavelength at pH 7. More HO· was formed at pH 6 than pH 7, but RCS showed the opposite pH-dependency. The findings in this study provide the fundamental information in selecting UV-LEDs with specific wavelength for enhancing/optimizing chlorine photodecay and/or its radical generation at different pHs in real-world applications. Highlights: UV-LEDs at four wavelengths were used for chlorine photodecay and radical formation. HOCl/OCl − photodecay was influenced more by molar absorptivity than quantum yield. An empirical model was built to predict chlorine photodecay rates. The wavelength dependency was larger at alkaline pH than at acidic pH. More HO· and ClO· were formed at shorter (longer) wavelength at pH 6 (7).